Analysis and prediction of marine heatwaves in the Western North Pacific and Chinese coastal region - Yang, Yifei; Sun, Wenjin; Yang, Jingsong; Lim Kam Sian, Kenny T. C.; Ji, Jinlin; Dong, Changming (Frontiers in Marine Science, 2022)
Over the past decade, marine heatwaves (MHWs) research has been conducted in almost all of the world’s oceans, and their catastrophic effects on the marine environment have gradually been recognized. Using the second version of the Optimal Interpolated Sea Surface Temperature analysis data (OISSTV2) from 1982 to 2014, this study analyzes six MHWs characteristics in the Western North Pacific and Chinese Coastal region (WNPCC, 100°E ∼ 180°E, 0° ∼ 65°N). MHWs occur in most WNPCC areas, with an average frequency, duration, days, cumulative intensity, maximum intensity, and mean intensity of 1.95 ± 0.21 times/year, 11.38 ± 1.97 days, 22.06 ± 3.84 days, 18.06 ± 7.67 °Cdays, 1.84 ± 0.50°C, and 1.49 ± 0.42 °C, respectively, in the historical period (1982 ~ 2014). Comparing the historical simulation results of 19 models of the Coupled Model Intercomparison Project Phase 6 (CMIP6) with the OISSTV2 observations, five best-performing models (GFDL-CM4, GFDL-ESM4, AWI-CM-1-1-MR, EC-Earth3-Veg, and EC-Earth3) are selected for MHWs projection (2015 ~ 2100). The MHWs characteristics projections from these five models are analyzed in detail under the Shared Socio-economic Pathway (SSP) 1-2.6, 2-4.5 and 5-8.5 scenarios. The projected MHWs characteristics under SSP5-8.5 are more considerable than those under SSP1-2.6 and 2-4.5, except for the MHWs frequency. The MHWs cumulative intensity is 96.36 ± 56.30, 175.44 ± 92.62, and 385.22 ± 168.00 °Cdays under SSP1-2.6, 2-4.5 and 5-8.5 scenarios, respectively. This suggests that different emission scenarios have a crucial impact on MHW variations. Each MHWs characteristic has an obvious increasing trend except for the annual occurrences. The increase rate of MHWs cumulative intensity for these three scenarios is 1.02 ± 0.83, 3.83 ± 1.43, and 6.70 ± 2.61 °Cdays/year, respectively. The MHWs occurrence area in summer is slightly smaller than in winter, but the MHWs average intensity is stronger in summer than in winter.